Kebijakan Pemerintah Joko Widodo dan Jusuf Kalla Dalam Upaya Membangun Dialog Untuk Penyelesaian Konflik Vertikal Papua Tahun 2014-2019 - Aldiano Hadi Nugroho; Nur Hidayat Sardini (Journal of Politic and Government Studies, 2019)
ABSTRACTThis research was conducted to explain the government's efforts by Joko Widodo and Jusuf Kalla as an effort to establish a dialogue for Papua's vertical conflict resolution.This study uses a qualitative-descriptive research methodology because this study explains phenomena relating to current and experienced situations, attitudes and views that are present at the moment, the relationship between variables contradicts two or more conditions, the effect on a condition, and the difference between facts. This study is conducted by asking for information to the primary subject, namely the source and main informants and secondary subjects, as additional data sources, reinforced by literature. The data then explained the efforts made by the Government of Joko Widodo and Jusuf Kalla as an effort to establish a dialogue for resolving Papua's vertical conflict as a new government paradigm, it’s also approached establishing relationships with conflict actors and stakeholders supporting inter-Papuan consultations, helping Papua prepare a resolution process potential conflict with the central government, and understand the conflict between the government and pressure groups and separatist groups.The results of the study indicate that the Government policies of Joko Widodo and Jusuf Kalla in seeking dialogue on the resolution of Papua's vertical conflict have challenges. The dialogue paradigm that has misconceptions, where dialogue as a concept and approach that has not been properly understood, and factors that influence dialogue efforts on vertical conflict resolution in Papua have not succeeded where the history of integration and identity, political violence, development failure, and marginalization of Papuans as the root the problems that occur in Papua and West Papua have not been resolved completely by the government.In the future the Government of Joko Widodo and Jusuf Kalla needs to re-consolidate state institutions that run solitary and inconsistent in understanding dialogues that are not biased. The governments of Joko Widodo and Jusuf Kalla also need to have a long-term main strategy in making projections of various aspects and dimensions that have connections between one another to be in harmony and not fragmented.Keywords: Dialogue, Conflict Resolution, Papua, Joko Widodo's Government